Transient Potassium Channels: Therapeutic Targets for Brain Disorders - Noh, Wonjun; Pak, Sojeong; Choi, Geunho; Yang, Sungchil; Yang, Sunggu (Frontiers in Cellular Neuroscience, 2019)
Transient potassium current channels (IA channels), which are expressed in most brain areas, have a central role in modulating feedforward and feedback inhibition along the dendroaxonic axis. Loss of the modulatory channels is tightly associated with a number of brain diseases such as Alzheimer's disease, epilepsy, fragile X syndrome, Parkinson’s disease, chronic pain, tinnitus, and ataxia. However, the functional significance of IA channels in these diseases has so far been underestimated. In this review, we discuss the distribution and function of IA channels. Particularly, we posit that downregulation of IA channels results in neuronal (mostly dendritic) hyperexcitability accompanied by imbalanced excitation and inhibition ratio in the brain's networks, eventually causing the brain diseases. Finally, we propose a potential therapeutic target: the enhanced action of IA channels to counteract Ca2+-permeable channels including NMDA receptors could be harnessed to restore dendritic excitability, leading to a balanced neuronal state.